Bat Dentitions: A Model System for Studies at the Interface of Development, Biomechanics, and Evolution. (16th May 2022) - Santana, Sharlene E; Grossnickle, David M; Sadier, Alexa; Patterson, Edward; Sears, Karen E
Abstract: The evolution of complex dentitions in mammals was a major innovation that facilitated the expansion into new dietary niches, which imposed selection for tight form–function relationships. Teeth allow mammals to ingest and process food items by applying forces produced by a third-class lever system composed by the jaw adductors, the cranium, and the mandible. Physical laws determine changes in jaw adductor (biting) forces at different bite point locations along the mandible (outlever), thus, individual teeth are expected to experience different mechanical regimes during feeding. If the mammal dentition exhibits functional adaptations to mandible feeding biomechanics, then teeth are expected to have evolved to develop mechanically advantageous sizes, shapes, and positions. Here, we present bats as a model system to test this hypothesis and, more generally, for integrative studies of mammal dental diversity. We combine a field-collected dataset of bite forces along the tooth row with data on dental and mandible morphology across 30 bat species. We (1) describe, for the first time, bite force trends along the tooth row of bats; (2) use phylogenetic comparative methods to investigate relationships among bite force patterns, tooth, and mandible morphology; and (3) hypothesize how these biting mechanics patterns may relate to the developmental processes controlling tooth formation. We find that bite force variation along the tooth row is consistent with predictions from lever mechanics models, with most species having the greatest bite force at the first lower molar. The cross-sectional shape of the mandible body is strongly associated with the position of maximum bite force along the tooth row, likely reflecting mandibular adaptations to varying stress patterns among species. Further, dental dietary adaptations seem to be related to bite force variation along molariform teeth, with insectivorous species exhibiting greater bite force more anteriorly, narrower teeth and mandibles, and frugivores/omnivores showing greater bite force more posteriorly, wider teeth and mandibles. As these craniodental traits are linked through development, dietary specialization appears to have shaped intrinsic mechanisms controlling traits relevant to feeding performance.